The role of fintech in mitigating information friction in supply chain finance. - Lee, Hsiao-Hui ([Manila] Asian Development Bank, 2019)
Recent advances in fintech, such as blockchain and artificial intelligence, could help improve the efficiency of supply chain finance. Double marginalization makes a banks optimal fintech investment level lower than the socially optimal level. This calls for mechanisms to incentivize or complement banks investment in fintech.
Keywords: Financial institutions; Banks and banking; Electronic books